If it's not what You are looking for type in the equation solver your own equation and let us solve it.
43x+19=-24
We move all terms to the left:
43x+19-(-24)=0
We add all the numbers together, and all the variables
43x+43=0
We move all terms containing x to the left, all other terms to the right
43x=-43
x=-43/43
x=-1
| 40=-10y^2 | | -4(x-2)=-20 | | (2x+1)*(x-2)=63 | | X=x^2+7x+3 | | -65a+-4a=2a+1,0262a | | x+3*x+5=26 | | 5(10x+9)=395 | | 2s+3s=-7 | | 2(9x-12)=66 | | 5(8x)=160 | | 9(x+4)=4(x-6) | | 0.3x^2-2.1x+3=x^2 | | 11x+14=124 | | 2x-5=6x-12 | | 6x-12=2x-5 | | 6x10=40+ | | 15n=3n+50 | | 6n=10n+16 | | 6x+7/3+2=4x+5/2x+3 | | 8n+2=24 | | x+9(2+4)=60 | | x²-14=0 | | 8x-10=6+4x | | 10+5y=18-11y | | 3^x+6=12 | | 18x^2=4 | | 11–3x=21–8x | | 3*x+6=12 | | 12z/7-42=21-3z/7 | | 3y=105 | | -t^2-3t+24=0 | | 4r-10=-50 |